1993
DOI: 10.1021/np50099a008
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Furanonaphthoquinones from Crescentia cujete

Abstract: Bioassay-directed fractionation of the MeCOEt extract of Crescentia cujete (Bignonaceae) resulted in the isolation of (2S,3S)-3-hydroxy-5,6-dimethoxydehydroiso-alpha-lapachone [1], (2R)-5,6-dimethoxydehydroiso-alpha-lapachone [2], (2R)-5-methoxydehydroiso-alpha-lapachone [3], 2-(1-hydroxyethyl)naphtho[2,3-b]furan-4,9-dione [4], 5-hydroxy-2-(1-hydroxyethyl)naphtho[2,3-b]furan-4,9-dione [5], 2-isopropenylnaphtho[2,3-b]furan-4,9-dione [6], and 5-hydroxydehydroiso-alpha-lapachone [7]. Compounds 1-3 are new, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 6 publications
0
29
0
2
Order By: Relevance
“…Especially 1 H-NMR and 13 C-NMR assingnments of rac-1 were established by heteronuclear multiple bond connectivity (HMBC) correlations and were listed in Experimental.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially 1 H-NMR and 13 C-NMR assingnments of rac-1 were established by heteronuclear multiple bond connectivity (HMBC) correlations and were listed in Experimental.…”
Section: Resultsmentioning
confidence: 99%
“…12,13) Perusal of these reports prompted us to carry out the epoxidation of 3 with the Shi catalyst and Oxone in buffered media. 1,14) We obtained (R)-2 in good chemical yield with modest enantioselectivity (40% ee) (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, scopoletin 15 and esculatin 16 were found in nature and they have antiproliferative, antioxidant, and anti-inflammatory activities ( Figure 1). Dihydrofurocoumarins such as fercoprolone, 17 mutisicoumarin, 18 cyclobrachycoumarin, 19 and isoerlengefusciol 20 have been found in nature and they have similar activities to coumarin derivatives. We have also recently reported that some 3-cyano-4,5-dihydrofurans show antifungal and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some dehydroiso-α-lapachones 1a,b,b',f, having a 2-isopropenyl-2,3-dihydronaphtho- [2,3-b]furan-4,9-dione structure, were isolated from Cresentia cujete, and showed interesting mutagenic activities [2]. In this paper, one-step preparation of 2-isopropenyl-2,3-dihydronaphtho [2,3-b]furan-4,9-diones 1 are described.…”
mentioning
confidence: 99%